Innovative tools for hybrid seed production of vegetables - Kumar, Rajesh; Singh, P. M.; Bhardwaj, D. R.; Prasanna, H. C.; Chaubey, T.; Pandey, S.; Tiwari, S. K.; Singh, B. K.; Gautam, K. K.; Reddy, Y. S.; Mishra, Gyan P. (Indian Horticulture, 2019)
The choice of using F1 hybrid seeds in vegetable production is increasing worldwide owing to their yield potential, resistance, quality attributes and storability. Hybrid varieties have been developed in those vegetable crops which manifest distinct hybrid vigour. From the breeder’s point of view, development of hybrid cultivars allows better control of intellectual property rights including control and protection of parental lines. Although experimental crosses can be developed through manual emasculation (in case of hermaphrodite crops) followed by manual pollination of emasculated flowers or pistilate flowers (in case of monoecious crops with separate staminate and pistilate flowers), commercial seed production of hybrids is a costly affair. Availability of cost effective mechanism/method to produce large-scale F1 seeds exploiting selected parental lines is an important factor, which ultimately determines the commercial viability of the hybrid varieties. A number of mechanisms and methods have been evolved for the development of hybrids in vegetable crops, however, only selected tools are utilized to develop commercial hybrids of specific vegetables.